Exogenous ethylene for uniform mango ripening in low-cost ripening chamber - Chowdhury, Md Golam Ferdous; Islam, Robiul; Khan, Md Hafizul Haque; Shozib, Habibul Bari; Molla, Mohammad Mainuddin; Kabir, Md Sarowar; Uddin, Md Aslam; Khatun, Arifa (Asian-Australasian Journal of Food Safety and Security, 2025)
Demand for ripe fruit, especially mango, is increasing around the world due to its nutrients and delicious taste attributes. But commercial handling of mangoes fruits meets challenges due to irregular fruit ripening. A practical solution to tackle this issue could be the application of external ethylene to the physiologically matured mango fruit for its climacteric nature of respiration and ethylene rate. This study aimed to figure out the optimum ethylene concentration for mature mango uniform ripening and its efficacy on the fruit quality with shelf life. Ethylene works as a catalyst to accelerate ripening processing of climacteric fruits. Therefore, exogenous concentration liquid ethylene was applied on ‘BARI Aam-2’ mangoes at low-cost fruit ripening chamber where ethylene gas was released from a portable ethylene generator (Catalytic Generators, USA) into a ripening chamber. Physiologically matured mango (BARI Aam-2) was collected from Bagha at Rajshahi and uniform with defectless were randomly selected for experimentation. To ensure uniform ripening, ethylene was applied per liter capacity for specific durations such as 1 min (50 ppm), 2 min (100 ppm), and 3 min (150 ppm) with concentrations verified using a gas analyzer (IAQ22080143). Among them, mango treated with 100 ppm to 150 ppm ethylene accelerated the highest peak of respiration indicating accelerated metabolic activity, while membrane permeability increased over time. Fruit firmness declined across all treatments, with similar softening levels by Day 8. The total soluble solids (TSS) levels peaked at 100 ppm and 150 ppm treatments, enhancing sweetness and carbohydrate metabolism. The study concludes that 100 ppm ethylene optimally balances ripening, sweetness, and nutrient preservation while minimizing weight loss. This application of optimum exogenous ethylene effectively regulated the ripening process of physiologically matured mango, with moderate concentration promoting desirable ripening as per the market demand and maintaining postharvest quality which ensure the produce safe for consumption. Asian Australas. J. Food Saf. Secur. 2025, 9(2), 57-66